Peran Guru PAI dalam Menumbuhkan Rasa Cinta Tanah Air Pada Siswa Mts Arrabi Tamansuruh - Slamet Slamet; Mar Syahid (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to examine the role of PAI teachers in fostering a sense of love for the homeland and PAI Teacher Assessment in forming the character of patriotism in students at MTS Arrabi Tamansuruh. The method used is descriptive qualitative research. Three data collection techniques applied in this research include interviews, observation, and documentation. The research was conducted at MTS Arrabi Tamansuruh. Data were analyzed using interactive analysis methods. The research results show that PAI teachers have an important role in helping students develop a sense of love and pride for their homeland, as well as preparing them to become responsible citizens and make positive contributions to nation-building.